Assessing the gender dimensions in the true costs of food production in Kenya - Geoffrey, Baragu; Boukaka, Sedi Anne; Benfica, Rui (International Food Policy Research Institute, 2024)
Key takeaways: Gender-based environmental and social external costs create substantial economic inefficiencies in the agricultural sector. The gender wage gap contributes 12.8% to total external costs. Women's limited access to resources leads to reduced productivity, with female farmers investing 36% less in inputs than their male counterparts. Workplace harassment, which disproportionately affects women, accounts for 10.8% of total external costs. Unequal land management practices (women managing smaller plots) and having restricted access to improved agricultural inputs create additional inefficiencies in resource allocation and production outcomes.